PERANCANGAN SISTEM INFORMASI KEHADIRAN MAHASISWA MENGGUNAKAN FINGERPRINT DAN PHP DI PROGRAM STUDI INFORMATIKA UNIVERSITAS MUHAMMADIYAH SEMARANG - Safuan Safuan; Luqman Assaffat (Pusat Riset dan Inovasi Nasional, 2022)
The need for student attendance information on campus is the main factor of success academic process. Often there are validation and identification errors in student attendance process (human error or manipulation process) and the slowness of the information obtained, because attendance is recorded manually in every class. This has an impact on the success of the academic process directly and society at large. Due to the importance of attendance information, various research has offered a system in the student attendance process, with various technology. One of the popular technologies and believed to validate and identify well are fingerprints. Therefore, this paper proposes the introduction of absenteeism system on campus by utilizing fingerprint technology that is integrated with PHP programming and MySQL database. This research uses Fingerprint FP Personnel Revo V4.0 as a means of identifying student data when absent. The system will display student attendance quickly so that the attendance recapitulation process can be obtained in a short time. This system is applied to the Informatics study program at the Faculty of Engineering, University of Muhammadiyah Semarang